2021
DOI: 10.1111/cns.13688
|View full text |Cite
|
Sign up to set email alerts
|

TROAP regulates cell cycle and promotes tumor progression through Wnt/β‐Catenin signaling pathway in glioma cells

Abstract: Aims Experimental evidence demonstrated a crucial role of TROAP (Trophinin‐associated protein) in regulating the cell proliferation of multiple tumors, while TROAP expression and function were largely unknown in glioma. We aimed to investigate the oncogenic role of TROAP and its potential mechanisms in gliomagenesis. Methods Four gene expression databases (GEO, TCGA, GTEx and CCLE) were enrolled in our study and used for TROAP expression and survival analysis. TROAP expression was quantified by qRT‐PCR, wester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 34 publications
3
29
0
Order By: Relevance
“…Recently, Jing et al demonstrated that TROAP knockdown in gastric cancer cells results in reduced tumor cell growth, migration and invasion (36). Emerging evidence indicates that positive proliferation related gene, such as cyclin D1, survivin, and p-AKT, are positively regulated by TROAP (24)(25)(26). In the current study, we revealed TROAP as a downstream target of METTL14.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Recently, Jing et al demonstrated that TROAP knockdown in gastric cancer cells results in reduced tumor cell growth, migration and invasion (36). Emerging evidence indicates that positive proliferation related gene, such as cyclin D1, survivin, and p-AKT, are positively regulated by TROAP (24)(25)(26). In the current study, we revealed TROAP as a downstream target of METTL14.…”
Section: Discussionsupporting
confidence: 60%
“…Although METTL14 overexpression decreased the proliferation of SKOV-3 cells (Figure 5E), the overexpression of TROAP reversed this inhibitory effect on cell proliferation in the SKOV-3 and A2780 cells (Figure 5E and Supplementary Figure S3). We next evaluated the expression of TROAP target genes, such as cyclin D1, survivin, and p-AKT, because their downregulation may also be involved in the inhibition of ovarian cancer cell proliferation due to METTL14 (24)(25)(26). As expected, the exogenous expression of METTL14 downregulated the expression levels of cyclin D1, survivin, and p-AKT.…”
Section: Mettl14 Inhibited Ovarian Cancer Cell Proliferation By Targe...mentioning
confidence: 83%
“…Proteins such as heterochromatin, including cell surface protein, have a role in apoptosis. G1/S Progression search yielded two studies, one of which identified an important role of TROAP in cell cycle regulation and enhanced tumour progression [ 58 ]. Cell Cycle Progression search yielded 19 articles relevant to cell cycle progression.…”
Section: Resultsmentioning
confidence: 99%
“…Upregulation of Wnt/β‐catenin might thus increase the risk of tumor generation or growth. It has been reported that Wnt/β‐catenin signaling plays an important role in prostate cancer and glioma, promoting self‐renewal or expansion 44,45 . In contrast, melanoma growth is slowed by the activation of Wnt/β‐catenin signaling 46 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that Wnt/β-catenin signaling plays an important role in prostate cancer and glioma, promoting self-renewal or expansion. 44,45 In contrast, melanoma growth is slowed by the activation 46 It is worth noting that although the role of Wnt/β-catenin signaling in tumor development is still controversial, tumor progression is a long-term process, in contrast to the acute onset of cerebral hemorrhage. In addition, Wnt/β-catenin signaling also plays an important role in vascular repair after traumatic brain injury.…”
Section: Discussionmentioning
confidence: 99%